1977
DOI: 10.1073/pnas.74.8.3547
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-binding ligands in milk and intestine: a role in neonatal nutrition?

Abstract: The hythesis that a zinc-binding ligand (ZBL) recently discovered in human milk but absent from cow's milk might be related to zinc nutrition in the neonate was investigated. The zinc-binding characteristics of rat milk were examined to determine if the rat was a suitable model. By gel filtration, rat milk was found to contain a ZBL with characteristics similar to those of the ZBL found in human milk. A similar ZBL was identified in the intestinal mucosa of rats 16 days of age and older but was absent in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 13 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…The high tissue to medium ratio of 65Zn which was demonstrated in vitro at the time of the first balance exceeded our previously reported ratios in patients with acrodermatitis enteropathica and control subjects.9 This suggests that zinc deficiency induces an adaptive mucosal response analogous to the increased in vitro mucosal uptake of iron which occurs in patients with iron deficiency.14 It has been proposed that human milk contains a ligand which facilitates zinc absorption and that the concentration of this ligand declines during lactation.5 15 Studies in the newborn rat suggest that this ligand no longer enhances zinc absorption after the intestinal mucosa has developed its own intrinsic ligand.5 Our in vitro study, while indicating that our patient's jejunal mucosa was able to concentrate 65Zn, does not exclude the possibility that a quantitative or a qualitative abnormality of such a ligand in the mother's breast milk impaired his in vivo absorption of zinc.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The high tissue to medium ratio of 65Zn which was demonstrated in vitro at the time of the first balance exceeded our previously reported ratios in patients with acrodermatitis enteropathica and control subjects.9 This suggests that zinc deficiency induces an adaptive mucosal response analogous to the increased in vitro mucosal uptake of iron which occurs in patients with iron deficiency.14 It has been proposed that human milk contains a ligand which facilitates zinc absorption and that the concentration of this ligand declines during lactation.5 15 Studies in the newborn rat suggest that this ligand no longer enhances zinc absorption after the intestinal mucosa has developed its own intrinsic ligand.5 Our in vitro study, while indicating that our patient's jejunal mucosa was able to concentrate 65Zn, does not exclude the possibility that a quantitative or a qualitative abnormality of such a ligand in the mother's breast milk impaired his in vivo absorption of zinc.…”
Section: Discussionmentioning
confidence: 58%
“…The plasma zinc and copper rose to 22 tLmol/l (144 ,ug/100 ml) and 12 '6 ,Vmol/l (80 ,ug/100 ml) respectively and the plasma alkaline phosphatase activity to 305 lU/I. 4.7 ,tmol/l (30.7 ,ug/100 ml) (normal range [11][12][13][14][15][16][17][18][19][20][21][22][23][24] ,umol/l (72-157 ,tg/100 ml)) and 8-1 ,umol/l (51.5 tg/100 ml) (normal range 12-26 ,umol/l (76-165 ,ug/100 ml)) respectively. Total serum protein was 0-54 g/100 ml with an albumin content of 0-38 g/100 ml; the plasma alkaline phosphatase activity, a zinc-dependent enzyme, was 78 IU/I (normal range 71-247 IU/l).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have tried to explain this well-characterized difference and as of yet there is no consensus (please see ''Dietary Zinc'' below for further discussion). [50][51][52] The clinical presentation of AE is similar to deficiency dermatitis caused by low dietary zinc. For example, infants may develop a deficiency dermatitis identical to AE as a result of very low concentrations of zinc in their mother's milk.…”
Section: Clinical Manifestationsmentioning
confidence: 96%
“…Several studies have tried to explain this well-characterized difference between human breast milk and cow milk. [50][51][52] For example, it has been shown by gel chromatography that the zinc in cow milk is associated with the high moleculareweight fractions, whereas zinc in human milk is associated with a low moleculare weight fraction. 50 It is, therefore, likely that zinc is bound to different molecules in cow versus human milk.…”
Section: Dietary Zincmentioning
confidence: 98%
“…Gel chromatography indicated that most of the zinc in cow's milk was associated with HMM fractions, whereas zinc in human milk was associated with LMM fractions. A species difference in zinc-binding ligands may explain why symptoms of AE can be alleviated by feeding human but not cow's milk [50,51]. These studies initiated several investigations on the binding ligands of zinc and other elements in human or bovine milk [52][53][54][55][56][57][58][59][60][61][62][63][64][65], infant formula based on cow's milk [63], and in different biological fluids [66,67].…”
Section: Milkmentioning
confidence: 99%